Chloroquine mediated modulation of Anopheles gambiae gene expression - Abrantes, Patricia (2021)
Background: Plasmodium development in the mosquito is crucial for malaria transmission and depends on the parasite's interaction with a variety of cell types and specific mosquito factors that have both positive and negative effects on infection. Whereas the defensive response of the mosquito contributes to a decrease in parasite numbers during these stages, some components of the blood meal are known to favor infection, potentiating the risk of increased transmission. The presence of the antimalarial drug chloroquine in the mosquito's blood meal has been associated with an increase in Plasmodium infectivity for the mosquito, which is possibly caused by chloroquine interfering with the capacity of the mosquito to defend against the infection. Methodology/Principal Findings: In this study, we report a detailed survey of the Anopheles gambiae genes that are differentially regulated by the presence of chloroquine in the blood meal, using an A. gambiae cDNA microarray. The effect of chloroquine on transcript abundance was evaluated separately for non-infected and Plasmodium berghei-infected mosquitoes. Chloroquine was found to affect the abundance of transcripts that encode proteins involved in a variety of processes, including immunity, apoptasis, cytoskeleton and the response to oxidative stress. This pattern of differential gene expression may explain the weakened mosquito defense response which accounts for the increased infectivity observed in chloroquine-treated mosquitoes. Conclusions/Signifance: The results of the present study suggest that chloroquine can interfere with several putative mosquito mechanisms of defense against Plasmodium at the level of gene expression and highlight the need for a better understanding of the impacts of antimalarial agents on parasite transmission.